Occupational choices of women in South Africa. - Naidoo, Zaiboonnisha. (2010)
The purpose of this study is to determine women's perceptions and choices of different categories of occupations and the reasons for such choices. Since the installation of the first democratic post apartheid government in South Africa, national policy has advanced women's rights. Affirmative action has opened up opportunities previously closed to women, but there is little research documenting changes in career trends. The influence of race, gender, social and political changes on perceptions and choices of occupations of women in the country is not known. This study has focused on African and Indian females in the 15 to 60 age range in the greater Durban area. Women born between 1940 and 1985 have experience of the pre- and post apartheid era, and therefore changes in perceptions and choices could be investigated. A survey questionnaire was administered to 390 female learners in seven former Indian schools. Semi-structured interviews were conducted with 12 African and Indian women; six daughters in non - traditional occupations and six mothers in traditional occupations. The results from the survey and interviews suggest that women have a strong sense of empowerment and do not regard gender as a barrier to occupational choices. A limited number of occupations were categorized as suitable for men only, while the majority were deemed suitable for both men and women. Survey data indicated that African learners were more conservative in their choices than Indian learners. Interviews with the older women however, revealed that African women were more positive about opportunities open to them in the new South Africa. Detailed family profiles suggest that socio - economic factors rather than parental influence, impacted on decision-making patterns. The unique experiences of women in this country, who have been subject to political and social pressures of the apartheid policy and the rapid change of the post apartheid era, must be documented before any theoretical positions can be articulated about the career development of South African women. This study has contributed to research on the career development of women by providing some insight into how a sector of African and Indian women perceive and categorize occupations. === Thesis (Ph.D)-University of Durban-Westville, 2000.